Two Cases of Retroperitoneal Metastasis from a Completely Regressed Burned-Out Testicular Cancer. Issue 1 (January 2013) - Gurioli, Alberto; Oderda, Marco; Vigna, Dario; Peraldo, Francesca; Giona, Simone; Soria, Francesco; Cassenti, Adele; Pacchioni, Donatella; Gontero, Paolo
Introduction: Primary extragonadal germ cell tumors (EGCT) are rare and it is still a matter of debate if they have to be considered as primary extragonadal issues or metastases from a primary testicular neoplasm. We describe two cases of the so-called burned-out seminoma, a primary testicular germ-cell tumor that spontaneously regressed after demonstration of retroperitoneal metastases. Cases Presentation: Two patients (35 and 50 years old, respectively) presented with CT findings of retroperitoneal masses. In both cases physical examination of the testis was not suspicious, and only scrotal ultrasound (SUS) showed parenchymal alterations such as scarring, calcifications and nodular lesions. Left orchiectomy and chemotherapy were then performed in both cases. Currently, they are both free of disease. Conclusions: Although primary germ cell tumors may be of retroperitoneal origin, the likelihood of metastasis from a testicular primary origin should always be carefully considered in order to avoid misdiagnosis and to apply the best treatment schedule for the patients. Therefore, a testicular ultrasonography is mandatory in patients presenting CT findings of retroperitoneal adenopathy, even if patients are completely asymptomatic and their physical examination appears normal.